2015
DOI: 10.1371/journal.pone.0146183
|View full text |Cite
|
Sign up to set email alerts
|

Transient Exposure of Enalapril Normalizes Prenatal Programming of Hypertension and Urinary Angiotensinogen Excretion

Abstract: Maternal low protein diet programs offspring to develop hypertension as adults. Transient exposure to angiotensin converting enzyme inhibitors or angiotensin II receptor blockers can result in improvement in hypertension. Male rats whose mothers received a low protein diet during the last half of pregnancy were given either vehicle, continuous enalapril (CE) in their drinking water or were given transient enalapril exposure (TE) after weaning at 21 days of age. The TE group had enalapril in their drinking wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 46 publications
2
40
2
Order By: Relevance
“…30 Washburn et al found increased plasma aldosterone levels in male adolescents born to mothers with preeclampsia. 8 In animal experiments, the offspring from dams with protein restriction, 11,12 diabetes 19 or inflammation 20 showed significant increases in intrarenal RAAS components such as angiotensinogen and ANG II, renal and arterial proinflammatory cytokines and pulmonary and plasma ACE activity, which were associated with higher BP in these offspring. However, not all studies involving treatments increasing the BP of pregnant dams have reported increased basal BP in the offspring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Washburn et al found increased plasma aldosterone levels in male adolescents born to mothers with preeclampsia. 8 In animal experiments, the offspring from dams with protein restriction, 11,12 diabetes 19 or inflammation 20 showed significant increases in intrarenal RAAS components such as angiotensinogen and ANG II, renal and arterial proinflammatory cytokines and pulmonary and plasma ACE activity, which were associated with higher BP in these offspring. However, not all studies involving treatments increasing the BP of pregnant dams have reported increased basal BP in the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…RD or chronic blockade of the RAAS and inflammation has been demonstrated to reduce elevated BP through restoration of renal and arterial function in offspring of dams after different types of insult to the mother during pregnancy. 11,12,1416,20 Mizuno et al demonstrated that the RAAS plays a significant role not only in the generation of increased basal BP but also in the development of the enhanced renal sympathetic and pressor responses to physical stress in prenatally programmed adult hypertensive rats. 17,18 Based on such observations, we investigated whether disrupting the integrity of the renal nerves or of the RAAS would alter the maintenance of sensitization of ANG II-induced hypertension in offspring of HT dams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were trained for four consecutive days by placing them in a large Lucite container and inflating a cuff around its tail several times (Mansuri et al. ; Mizuno et al. , ).…”
Section: Methodsmentioning
confidence: 99%
“…The investigator measuring the blood pressure (J.J.) was blinded as to whether the rat was from the vehicle or the dexamethasone group. Rats were trained for four consecutive days by placing them in a large Lucite container and inflating a cuff around its tail several times (Mansuri et al 2015;Mizuno et al 2014Mizuno et al , 2013. We then measured the blood pressure on the fifth day using a CODA Blood Pressure Non-Invasive Pressure Analyzer (Kent Scientific Corporation, Torrington, CT).…”
Section: Blood Pressurementioning
confidence: 99%